Pendampingan Guru Dalam Pembelajaran Bahasa Inggris Menggunakan Mentimeter Platform di SMA Negeri 12 Makassar - Suryani Munir, Fairus; Sukmawati, Sukmawati; Rahmayanti, Andi; Sakkir, Geminastiti; Noni, Nurdin (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Mentoring in learning through Mentimeter Platform is highly essential for english teachers at SMA Negeri 12 Makassar. The unavailability of integrated technology-based learning media highlights the need to enhance teachers' creativity and the quality of learning, which must be addressed urgently. This training aims to boost teachers' creativity in developing IT-based English-learning media. This community service program adopts the Interactive Teaching and Learning method, using interviews as an instrument with a sample of 5 English teachers who also served as respondents in the activity through purposive sampling. The results of the program indicate improvements in teachers' skills in using Mentimeter and transforming conventional teaching materials into interactive, technology-based learning media. This progress was supported by students' enthusiasm, along with their high interest and motivation to engage with the learning English materials delivered by teachers using the Mentimeter platform. Moreover, the students’ active participation during the activities provided positive feedback and evaluations for the teachers, encouraging them to be more innovative and creative in designing technology-integrated materials and media. Students expressed a desire for more interactive and enjoyable learning experiences, which they found helpful in better understanding the material and actively participating in the learning process.